1986
DOI: 10.1271/bbb1961.50.3181
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric hydrolysis of aryloxyacetaldehyde cyanohydrin acetates.

Abstract: Cyanohydrins are considered to be versatile synthons in organic synthesis because they can be readily converted to a-hydroxycarboxylic acids,1} oc-hydroxyaldehydes2) and ethanolamine derivatives,3) which include a number of physiologically active compounds. Lactic acid, tartaric acid, ephedrine and /?-adrenergic blocking agents are the representative examples of these classes of compounds. Thus, synthesis of chiral cyanohydrins is considered to be an interesting and useful problem, but only a very few reports … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1988
1988
2002
2002

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…6 ) We have investigated asymmetric hydrolysis of l-cyanoalkyl acetates, because it was supposed that esterases would show wide substrate specificities. 7 ) In the course of our studies, 8) Matsumoto and Ohno have demonstrated that a lipase produced by a Pseudomonas sp. selectively hydrolysed (R)-enantiomers of 2-aryloxy-I-cyanoethyl acetates.…”
mentioning
confidence: 86%
“…6 ) We have investigated asymmetric hydrolysis of l-cyanoalkyl acetates, because it was supposed that esterases would show wide substrate specificities. 7 ) In the course of our studies, 8) Matsumoto and Ohno have demonstrated that a lipase produced by a Pseudomonas sp. selectively hydrolysed (R)-enantiomers of 2-aryloxy-I-cyanoethyl acetates.…”
mentioning
confidence: 86%
“…By localizing in a single plasmid the genes encoding the enzymes transketolase and 3-deoxy-~-arabinoheptulosonate synthase, biocatalysis previously exploited in the multi-step, immobilized enzyme synthesis of DAHP ( 107) is reconstructed in an intact microbial cell. In this reaction sequence, fructose-6-phosphate (1 14) is converted into erythrose-4-phosphate (1 15) under the action of transketolase, followed by coupling of (115) with phosphoenol pyruvate (116) in the presence of DAHP synthase to yield DAHP (107). This plasmid biocatalysis takes advantage of the long overlooked impact of transketolase activity on the flow of carbon into aromatic amino acid biosynthesis.…”
Section: Miscellaneous Oxidationsmentioning
confidence: 99%
“…After the reaction was complete, the organic materials were extracted with diethyl ether (100ml x 3). The combined organic layer waså .dried over anhydrous Na2SO4 and evaporated under reduced pressure to afford a mixture of the starting acetate (4) and the hydrolyzed cyanohydrin (3). The products were purified Preparation of l-aryloxy-2,3-epoxypropane.…”
Section: Cultivationmentioning
confidence: 99%